The Degree of Monopoly - Tucker, Rufus S. (Quarterly Journal of Economics, 1940)
Journal Article The Degree of Monopoly Get access Rufus S. Tucker Rufus S. Tucker New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 55, Issue 1, November 1940, Pages 167–169, https://doi.org/10.2307/1881673 Published: 01 November 1940